Strategi Komunikasi Organisasi HMI dalam Rekrutmen Kaderisasi Anggota Baru di Fakultas Dakwah dan Komunikasi UIN Sumatera Utara - Malik, Imam; Yanti , Elfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The case of a victim of robbery who became a suspect in Medan City had caused This study aims to determine the organizational communication strategy of HMI in recruiting new member cadres at the Faculty of Da'wah and Communication in maintaining the existence of its organization at UIN Sumatra Utara. To find out the obstacles to the HMI organizational communication strategy in recruiting new member cadres at the Faculty of Da'wah and Communication in maintaining the existence of its organization at UIN Sumatra Utara. This type of research uses a qualitative approach to research, in an effort to provide answers to the problems that have been described, because it uses a descriptive qualitative approach. The collected data were analyzed using the Miles & Hubberman interactive model including: data reduction, data presentation, and drawing conclusions. The results of this study show basic findings such as the cadres of the Islamic Student Association (HMI) of UIN North Sumatra are able to have a positive impact on students where the cadres of the Islamic Student Association (HMI) hold meetings to maintain friendship among each HMI member, and are able to liven up the to promote open discussion on campu.